Prevalent clinical symptoms, comorbidities, and treatment outcomes among COVID-19 patients in Abuja, Nigeria - Elizabeth Musili Joseph-Shehu; A. N. Wojuola; Hamina Dathini (Nursing and Health Sciences Journal (NHSJ), 2025)
Comorbidities are medical conditions that coexist with the disease of interest but are unrelated in causality or aetiology to the primary diagnosis. Until recently, the influence of these coexisting medical conditions on the outcome of care for patients with specific disease conditions has often been ignored. This study aims to determine the prevalent clinical presentation, comorbidities, and treatment outcomes among COVID-19 patients in Abuja, Nigeria. The retrospective study design was employed to select 1056 COVID-19 patients from the three selected isolation centres in Abuja. Results indicate that the most prevalent clinical presentation was dry cough, 960 (91.2%), shortness of breath, 677 (64.3%), and fever, 615 (58.2%). Significant comorbidities in the overall population were Diabetes with Hypertension, with a frequency of 165 out of 547; Hypertension alone represented 123 out of 547, and diabetes alone 96 out of 547. Regarding the outcome of care, cumulatively, of the 1056 patients that participated in this study, 123 (11.6%) mortality was recorded while the cumulative survival rate was 933 (88.4%). Furthermore, the result indicates that mortality among patients with diabetes and hypertension was highest at 45 (4.3%), followed by patients with diabetes alone at 25 (2.4%). Within fatal cases, an estimated 98.1% had the presence of one or more comorbidities. There is a significant relationship (p-value ≤ 0.01) between the prognosis of COVID-19 patients with comorbidities and those without comorbidities. Therefore, awareness, education, and lifestyle modification are advocated for those at risk of COVID-19.